2012
DOI: 10.1016/j.tem.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional integration of mitochondrial biogenesis

Abstract: Gene regulatory factors encoded by the nuclear genome are essential for mitochondrial biogenesis and function. Some of these factors act exclusively within the mitochondria to regulate the control of mitochondrial transcription, translation and other functions. Others govern the expression of nuclear genes required for mitochondrial metabolism and organelle biogenesis. The peroxisome proliferator-activated receptor gamma coactivator-1 (PGC-1) family of transcriptional coactivators plays a major role in transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
569
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 697 publications
(590 citation statements)
references
References 96 publications
11
569
1
9
Order By: Relevance
“…multiple nuclear transcriptional regulators, including PGC-1a, PGC-1b, NRF1, GABP, PPARa, PPARd, and ERRs (13)(14)(15)(53)(54)(55). Perm1 also led to enhanced levels of PGC1a and ERRa, suggesting that the effects of Perm1 on gene expression are at least in part mediated through increases in these transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…multiple nuclear transcriptional regulators, including PGC-1a, PGC-1b, NRF1, GABP, PPARa, PPARd, and ERRs (13)(14)(15)(53)(54)(55). Perm1 also led to enhanced levels of PGC1a and ERRa, suggesting that the effects of Perm1 on gene expression are at least in part mediated through increases in these transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…The PGC-1 coactivators are key regulators of mitochondrial function and biogenesis (6,7). Studies over the past decade have shown that this family of inducible transcriptional coregulators serve to coordinately regulate the expression of nuclear and mitochondrial genes encoding enzymes and proteins involved in virtually all aspects of mitochondrial energy transduction and ATP synthesis in mitochondrion-rich tissues such as heart, brown adipose tissue, and skeletal muscle (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in cells and in mice have revealed the importance of the PGC-1 coactivators as "boosters" of transcription factors involved in the regulation of nuclear and mitochondrial genes encoding enzymes and proteins involved in mitochondrial energy transduction and ATP synthesis (6,7). Loss-and gainof-function studies in mice have demonstrated the importance of PGC-1␣ and -␤ in mitochondrial biogenesis in the developing heart and other mitochondrion-rich tissues (8 -13).…”
mentioning
confidence: 99%
“…However, an important regulatory control is the coordinated transcription of genes encoding for these proteins that will determine the rate of synthesis and cellular concentrations that will promote and contribute to mitochondrial mass. In mammalian cells, this transcriptional control involves the PGC-1 pathway and its interactions with transcription factors including NRFs and YY1 that are bound to promoters of mitochondrial import genes (Blattler et al 2012b;Scarpulla et al 2012). Whether there is selectivity or specificity among the different import pathways described here is currently unknown.…”
Section: Mitochondrial Protein Importmentioning
confidence: 97%
“…Another level of control of this mitochondrial transcriptional machinery is by inducing amounts of its components. Along these lines elements essential to mitochondrial transcription, such as TFAM, TFB2M, MTERF, and POLRMT, are regulated through the transcriptional coactivators PGC-1a and PGC-1b through their interaction with NRFs, ERRs, and YY1 (Mootha et al 2004;Blattler et al 2012b;Scarpulla et al 2012).…”
Section: Mitochondrial Transcriptionmentioning
confidence: 99%